2017
DOI: 10.3389/fpsyg.2017.00147
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the NEO-FFI Items: Parsing the Nature of Social Anhedonia Using the Revised Social Anhedonia Scale and the ACIPS

Abstract: The goal was to examine the nature of social anhedonia using two validated measures and study their relationship to scores on the NEO-Five Factor Inventory (NEO-FFI). Nearly 1,900 college-aged participants completed the Chapman Revised Social Anhedonia Scale (RSAS), Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS), and the NEO-FFI. Although both the RSAS and ACIPS were associated with the NEO-FFI domains of Extraversion, Agreeableness, and Neuroticism, linear regression analyses revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
2
15
0
1
Order By: Relevance
“…Further psychometric work is needed to understand the shared variance between these measures. For instance, Gooding et al (197) have reported that different aspects of personality predict scores on the ACIPS and the RSAS, suggesting subtle differences in what these two scales capture despite both being measures of social anhedonia. Furthermore, we need to begin to devise smart validity studies providing links to emotional and behavioral manifestations of social anhedonia.…”
Section: Discussionmentioning
confidence: 99%
“…Further psychometric work is needed to understand the shared variance between these measures. For instance, Gooding et al (197) have reported that different aspects of personality predict scores on the ACIPS and the RSAS, suggesting subtle differences in what these two scales capture despite both being measures of social anhedonia. Furthermore, we need to begin to devise smart validity studies providing links to emotional and behavioral manifestations of social anhedonia.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting for future work to consider SA within the broader context of personality. For example, SA has been consistently linked to introversion (Gooding, Padrutt, & Pflum, 2017; Kwapil et al, 2007), suggesting that this and other related constructs may be affected by and expressed through similar mechanisms. Epidemiological data may also speak to the extent to which SA does or does not overlap with other aspects of personality (Martin, Cicero, Bailey, Karcher, & Kerns, 2016), an important consideration for conceptualizing the nature of personality and for the assessment and treatment of personality disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Criterionrelated validity was evaluated by examining correlations between social anhedonia and social relationships (r=-.43, p<.001) [15]. The Cronbach's ⍺ was .86 in the previous study [20] and .81 in this study.…”
Section: ) Revised Social Anhedonia Scale (Rsas)mentioning
confidence: 65%